Prostatic collagen architecture in neutered and intact canines. Issue 11 (8th May 2018) - Ruetten, Hannah; Wegner, Kyle A.; Romero, Michael F.; Wood, Michael W.; Marker, Paul C.; Strand, Douglas; Colopy, Sara A.; Vezina, Chad M.
Abstract : Background: Prostate stiffness and increased collagen content both associate with the presence of urinary symptoms in men but mechanisms responsible, including impact of age and androgens, are unknown. Dogs develop prostate‐related urinary dysfunction similar to humans, but mechanisms are also unknown. Mice have been used to examine how prostatic collagen accumulation affects voiding but whether mouse prostatic collagen organization resembles human or dog has not been evaluated. Here, we have constructed the first comprehensive, comparative maps of collagen architecture in canine, human, and mouse prostate and test whether canine prostatic collagen content is increased by aging and reduced by castration. Methods: Complete transverse prostate sections were stained with picrosirius red and imaged with confocal microscopy to reveal and compare collagen architecture across species. Canine prostatic collagen fiber length, diameter, and density in prostatic urethral, periurethral, peripheral, and capsular regions were quantified and compared among four experimental groups: young intact, young neutered, old intact, and old neutered dogs. Results: Surprisingly, the majority of collagen was localized to the prostatic urethra in canine, human, and mouse. In canine and human, capsular regions also featured a dense collagen network but it appeared less dense than around prostatic urethra. Older, intact male canines exhibited overall denser prostate collagen fibers and had thicker capsular fibers than young, intact males. Prostatic glandular regions undergo dramatic atrophy and regression following castration, and our finding of neutered animals having increased collagen fiber density in both periurethral and peripheral regions is consistent with glandular contraction and increased proportion of stroma. Conclusions: Collagen architecture in dog appears similar to that in humans when cross sections are compared side‐by‐side. Canine collagen organization is affected by both age and androgen status, suggesting these factors may contribute to collagen accumulation in some males.